2009
DOI: 10.1371/journal.pone.0007462
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular and Intracellular Polyphenol Oxidases Cause Opposite Effects on Sensitivity of Streptomyces to Phenolics: A Case of Double-Edged Sword

Abstract: Many but not all species of Streptomyces species harbour a bicistronic melC operon, in which melC2 encodes an extracellular tyrosinase (a polyphenol oxidase) and melC1 encodes a helper protein. On the other hand, a melC-homologous operon (melD) is present in all sequenced Streptomyces chromosomes and could be isolated by PCR from six other species tested. Bioinformatic analysis showed that melC and melD have divergently evolved toward different functions. MelD2, unlike tyrosinase (MelC2), is not secreted, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…A recent study by Yang and Chen (2009) suggested that in the presence of plant phenolics, extracellular tyrosinase (MelC, which this study assayed for) may play a protective role by converting the phenols to toxic quinones which, in turn, would kill competing bacteria. The presence of a homologous bicistronic operon in streptomycetes, melD, was proposed to protect the tyrosinaseproducing strain against the potential toxic effect of the quinones (Yang and Chen 2009). The MelD type tyrosinases are not secreted and are in no way involved in melanin or melanoid pigment production.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study by Yang and Chen (2009) suggested that in the presence of plant phenolics, extracellular tyrosinase (MelC, which this study assayed for) may play a protective role by converting the phenols to toxic quinones which, in turn, would kill competing bacteria. The presence of a homologous bicistronic operon in streptomycetes, melD, was proposed to protect the tyrosinaseproducing strain against the potential toxic effect of the quinones (Yang and Chen 2009). The MelD type tyrosinases are not secreted and are in no way involved in melanin or melanoid pigment production.…”
Section: Discussionmentioning
confidence: 95%
“…As the completed genome sequences for various Streptomyces species become available, a bicistronic operon homologous to melC has been found in all the sequenced chromosomes, and has subsequently been named melD. 82 The melD operon also contains melD1 which is homologous to the melC2 gene encoding for the chaperone protein (Fig. 4).…”
Section: Tyrosinase and A Tyrosinase-like Protein With Phenoxazinone ...mentioning
confidence: 99%
“…In many bacteria, including Streptomyces spp., melanin serves as a natural marker for taxonomic identification up to the genus level [1][2][3]. Specifically, the production of melanin in Streptomyces was assigned to an adaptive response to elevated environmental stress conditions such as light, temperature, oxidative stress, as well as an elevated concentration of heavy metals [4][5][6]. In addition, melanin produced by Streptomyces spp.…”
Section: Introductionmentioning
confidence: 99%